Compensation incentives and heat exposure affect farm worker effort - Qianyao Pan (Public Library of Science (PLoS), 2021)
Farm workers are exposed to high risk of heat-related illness, especially when their jobs require working outside at a fast pace during hot days. Climate change has increased the number of days with high temperatures, and thereby the amount of time that farm workers are likely exposed to extreme heat. To better understand how high heat exposure affects farm workers, this study investigates how crop workers respond to heat exposure and estimates the effects of different pay and work arrangements on workers’ responses to heat exposure. We explore, specifically, whether piece-rate arrangements increase workers’ effort during periods with high heat exposure compared to workers paid by hourly wages. We use observational data from detailed measurements of localized heat exposure and individual workers’ effort in the field. First, these results show workers adjust their effort in response to heat exposure when the heat exposure level changes. Second, piece-rate arrangements increase workers’ effort during work shifts. Third, piece-rate arrangements allow workers to modify their effort more easily during different heat exposure levels. When facing low levels of heat exposure, workers who were paid by piece-rate arrangements exert a higher effort than workers paid by hourly wages, up until WBGT is 26.6˚C. When facing high levels of heat exposure (with WBGT exceeding 29.6˚C), workers paid by piece-rate arrangements lower their effort compared to workers paid by hourly wage arrangements.